Homomorphism and Isomorphism of Neutrosophic Over Topologized Graphs - G. Muthumari; R. Narmada Devi (Neutrosophic Sets and Systems, 2023)
In this paper introduce the homomorphism, isomorphism, weak isomorphism and co-weak isomorphism of Neutrosophic over topologized graphs. Some properties of isomorphism are introduced. The isomorphism of Neu trosophic over topologized graphs equivalnce relation, weak isomorphism of Neutrosophic over topologized graphs partial order relation and complement of Neutrosophic over topologized graphs also derived here.